Current Attitudes to Ageing as Reflected in the Names of Australian Aged Care Facilities. (September 2015) - Benczes, Réka; Burridge, Kate
Abstract : One of the most evolving areas of euphemisms in present-day society is ageing; our main hypothesis is that this process can be accurately studied through an analysis of the naming practices of aged care facilities. Accordingly, we examined the names of aged care facilities in the Melbourne region (Australia) from 2013 and compared this to the names used in 1987. We found that the 2013 sample showed a much greater degree of euphemistic usage as compared to the 1987 data. More specifically, the names in the 2013 data had a tendency to use the euphemistic strategy of full omission, and most often relied on conceptualizing the facility as either an upper-class family home or a holiday resort. Such strategies and conceptualizations were much less frequent in the 1987 data.